Pengembangan Perangkat Pembelajaran Matematika Berbasis Problem Based Learning Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas XI MIPA SMA - Elfira, Fitri; Syarifudin, Hendra (JEMS: Jurnal Edukasi Matematika dan Sains, 2022)
This study departs from the problem that students' mathematical problem solving abilities are still low. The low mathematical problem solving ability is caused by the lack of learning tools that can support the improvement of students' mathematical problem solving abilities. In addition, in general, the learning process does not fully support the activities of students and is still dominated by educators, so that students are not trained to build and develop their knowledge in finding their own mathematical concepts/procedures. It is hoped that through the development of this device, students' mathematical problem solving abilities can be improved. This type of research is a development study using the Plomp model, which consists of three phases, namely the preliminary phase, the prototyping phase and the evaluation phase. The resulting tools are lesson plans and problem-based learning worksheets for class XI MIPA SMA.